2013
DOI: 10.1038/aja.2012.171
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oncological treatments on semen quality in patients with testicular neoplasia or lymphoproliferative disorders

Abstract: Pretherapy sperm cryopreservation in young men is currently included in good clinical practice guidelines for cancer patients. The aim of this paper is to outline the effects of different oncological treatments on semen quality in patients with testicular neoplasia or lymphoproliferative disorders, based on an 8-year experience of the Cryopreservation Centre of a large public hospital. Two hundred and sixty-one patients with testicular neoplasia and 219 patients with lymphoproliferative disorders who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Bizet et al (2012) observed a significant lower total sperm count in patients with TC than that in patients with OC; all median parameters for each cancer type were in the normal WHO 1999 range, except for progressive motility. Two Italian studies showed the pre-freeze semen parameters were not impaired in the testicular neoplasia or in lymphoproliferative disorders (Gandini et al, 2003;Di Bisceglie et al, 2013). On the contrary, van Casteren et al (2010) showed, in 764 patients with different malignancies, that most male patients with cancer were at increased risk of an impaired semen quality; almost twothird of all semen samples was abnormal according to the reference values of the WHO guidelines 1999 (except brain tumours and non-Hodgkin lymphomas).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bizet et al (2012) observed a significant lower total sperm count in patients with TC than that in patients with OC; all median parameters for each cancer type were in the normal WHO 1999 range, except for progressive motility. Two Italian studies showed the pre-freeze semen parameters were not impaired in the testicular neoplasia or in lymphoproliferative disorders (Gandini et al, 2003;Di Bisceglie et al, 2013). On the contrary, van Casteren et al (2010) showed, in 764 patients with different malignancies, that most male patients with cancer were at increased risk of an impaired semen quality; almost twothird of all semen samples was abnormal according to the reference values of the WHO guidelines 1999 (except brain tumours and non-Hodgkin lymphomas).…”
Section: Discussionmentioning
confidence: 99%
“…Although the deleterious effects of chemotherapy and radiation are well documented (Trottmann et al, 2007;Diedrich et al, 2011), controversies exist about the effect of cancer itself on semen parameters before treatment. Most of the available studies do not consider the different types of cancers and mainly focused on testicular cancers and Hodgkin's disease, and data are heterogeneous and lack of comparison with men healthy and fertile.…”
Section: Introductionmentioning
confidence: 99%
“…Spermatogenesis is often impaired in testicular cancer patients prior to chemotherapy as a result of cancer itself (Di Bisceglie et al, 2013). In addition, PVB chemotherapy has substantial detrimental effects on spermatogenic function; most patients remain azoospermic or oligozoospermic for prolonged periods or are rendered permanently infertile (Schrader et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In the many years, following the increased success rate of cancer treatments, great efforts have been made to improve quality of life in survivors, including fertility preservation in young patients (Masopotova et al 2018). Because of their gonadotoxic effects, chemo-and radiotherapy can temporarily or permanently compromise fertility (Di Bisceglie et al 2013). Oncological treatments present severe gonadotoxic effects on both germ and Leydig cells.…”
Section: Introductionmentioning
confidence: 99%